Hospital quality improvement achieved by three parts of customer satisfaction - Inagaki, Haruo (The Journal of Japan Society for Health Care Management, 2008)
As we believe customer satisfaction (CS) can be achieved by solving problems of customer, patients for hospital can be considered as equivalent as customers for non-medical companies. CS in hospital management can be subdivided in three parts. The first part is satisfaction of patients and patients' families. The second part is satisfaction of affiliated private clinics, medical facilities or nursing facilities, which is equivalent of dealers' satisfaction (DS) for non-medical companies. The third is satisfaction in employees (ES). In Toyota memorial hospital, we consider these three parts of CS as most fundamental philosophy for hospital management. And the motto of “we are proud of our customers' smile with satisfaction” is listed first on our policies. In general, the purpose of organization management is to assure quality of products or services. In the same way, the purpose of hospital management is to assure quality of medical care and subsequently achieve these three parts of CS. For achieving CS, “policy management method” is applied in our hospital. In this policy management method, human resource development, which is how to improve employees' capacity, is involved as the biggest part. We introduce three specific examples of policy management for improvement of medical care in our hospital. The first is encouragement of trans-sectional activity. The second is arrangement of organ-based specialty center. The third is application of clinical indicator.